Hyper-stimulation of Pyrococcus furiosus CRISPR DNA uptake by a self-transmissible plasmid - Elizabeth A. Watts; Sandra C. Garrett; Ryan J. Catchpole; Landon M. Clark; Brenton R. Graveley; Michael P. Terns (Extremophiles, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The global distribution and evolutionary history of the pT26‐2 archaeal plasmid family - Catherine Badel; Gaël Erauso; Annika L. Gomez; Ryan Catchpole; Mathieu Gonnet; Jacques Oberto; Patrick Forterre; Violette Da Cunha (Environmental Microbiology, 2019)
Summary Although plasmids play an important role in biological evolution, the number of plasmid families well‐characterized in terms of geographical distribution and evolution remains limited, especially in archaea. Here, we describe the first systematic study of an archaeal plasmid family, the pT26‐2 plasmid family. The in‐depth analysis of the distribution, biogeography and host–plasmid co‐evolution patterns of 26 integrated and 3 extrachromosomal plasmids of this plasmid family shows that they are widespread in Thermococcales and Methanococcales isolated from around the globe but are restricted to these two orders. All members of the family share seven core genes but employ different integration and replication strategies. Phylogenetic analysis of the core genes and CRISPR spacer distribution suggests that plasmids of the pT26‐2 family evolved with their hosts independently in Thermococcales and Methanococcales, despite these hosts exhibiting similar geographic distribution. Remarkably, core genes are conserved even in integrated plasmids that have lost replication genes and/or replication origins suggesting that they may be beneficial for their hosts. We hypothesize that the core proteins encode for a novel type of DNA/protein transfer mechanism, explaining the widespread oceanic distribution of the pT26‐2 plasmid family.

A series of new E. coli–Thermococcus shuttle vectors compatible with previously existing vectors - Ryan Catchpole; Aurore Gorlas; Jacques Oberto; Patrick Forterre (Extremophiles, 2018)

The Case for an Early Biological Origin of DNA - Anthony M. Poole; Nobuyuki Horinouchi; Ryan J. Catchpole; Dayong Si; Makoto Hibi; Koichi Tanaka; Jun Ogawa (Journal of Molecular Evolution, 2014)